Scandinavian Background of Greek Mythic Cosmography: The Sun’s Water Transport - Panchenko, Dmitri (Hyperboreus, 2013)
Many Greek poets, including very early ones, referred to the sun’s night journey in a cup-like device. Most of them spoke of the ‘cup’; the poet of the Titanomachia, followed by other writers, called it the ‘cauldron’. Mimnermus described it as a ‘winged hollow bed’, but Athenaeus may be right in interpreting Mimnermus’ words as a hint at the hollow shape of a cup. The only detailed exposition of Helios’ daily voyage comes from Mimnermus. It includes nontrivial idea of the Sun’s god changing vehicle. During the day Helios travels in a chariot and during the night he uses a ‘winged hollow bed’ to sail from the place of the sunset to the place of the sunrise. It is argued in this paper that the motif of the sun’s night journey in a cup-like device originated either in the Danube region or in Scandinavia and that the motif of the Sun’s god changing vehicle is of Scandinavian provenance.